2012
DOI: 10.1037/a0028063
|View full text |Cite
|
Sign up to set email alerts
|

How do therapists ally with adolescents in family therapy? An examination of relational control communication in early sessions.

Abstract: Sequential analyses examined associations between the working alliance and therapist-adolescent communication patterns in 10 Spanish cases of brief conjoint family therapy. Early sessions with strong versus problematic alliances, rated by observers, were selected for coding of relational control communication patterns. No differences were found in the frequency of exchanges, but competitive responding by the therapists (reflecting an interpersonal struggle for control) was significantly more likely in problema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…This enabled them to more easily discuss health issues that can be often personal and sensitive. Humanistic engagement of health care providers helped to foster trust from young clients which was characterized as sincere caring, being empathetic, respectful, not objectifying, being honest, making them feel worthy of time and effort, and being open and friendly (Binder et al, 2011;Britto et al, 2010;Hudson et al, 2008;Klostermann et al, 2005;de la Pena, Friedlander, Escudero, & Heatherington, 2012;Rutherford, Pitetti, Zuckerbraun, Smola, & Gold, 2010;Schaeuble et al, 2010). All these attributes contain some degree of underlying quality of an authentic intention to care and respect these young clients (2011).…”
Section: Trust and Sense Of Emotional Safety Was A Prerequisite For Omentioning
confidence: 99%
“…This enabled them to more easily discuss health issues that can be often personal and sensitive. Humanistic engagement of health care providers helped to foster trust from young clients which was characterized as sincere caring, being empathetic, respectful, not objectifying, being honest, making them feel worthy of time and effort, and being open and friendly (Binder et al, 2011;Britto et al, 2010;Hudson et al, 2008;Klostermann et al, 2005;de la Pena, Friedlander, Escudero, & Heatherington, 2012;Rutherford, Pitetti, Zuckerbraun, Smola, & Gold, 2010;Schaeuble et al, 2010). All these attributes contain some degree of underlying quality of an authentic intention to care and respect these young clients (2011).…”
Section: Trust and Sense Of Emotional Safety Was A Prerequisite For Omentioning
confidence: 99%
“…“How do in‐session therapist behaviors contribute to strong and weak alliances with couples and families?” is undoubtedly an essential research question; however, only a few studies approached that question, and they used quite different research designs. One study (Thomas, Werner‐Wilson, & Murphy, ) using the Working Alliance Inventory‐Couples (Symonds & Horvath, ), and another five studies, using the same instrument utilized in the present study, the System for Observing Family Therapy Alliances (SOFTA; Friedlander, Escudero, Horvath, et al., ), assessed therapists’ alliance‐related behaviors within sessions (Escudero et al., ; Friedlander, Lee, Shaffer, & Cabrera, ; Lambert, Skinner, & Friedlander, ) or within cases over time (Friedlander, Lambert, Escudero, & Cragun, ; Muñiz de la Peña, Friedlander, Escudero, & Heatherington, ). One of those studies found that stable and deteriorating alliances were reflected in the relational control dynamics observed between therapists and their adolescent clients (Muñiz de la Peña et al., ); however, none focused its analysis on the possible differences associated with how the clients were referred to therapy and their (in)voluntary status.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on brief family therapy has confirmed that competitive symmetry in therapeutic interactions is associated with bad therapeutic alliances (de la Peña et al, 2012) and with less engagement in therapy (Cabero, 2004). The implication is that solution-focused therapists should monitor their conversations with clients moment by moment and take any unfolding competitive symmetrical patterns as a sign that the therapeutic alliance might be deteriorating.…”
Section: Therapeutic Interaction Dropout and Compliance With Homewomentioning
confidence: 94%
“…The implication is that solution-focused therapists should monitor their conversations with clients moment by moment and take any unfolding competitive symmetrical patterns as a sign that the therapeutic alliance might be deteriorating. If such patterns appear, a good antidote might be introducing more one-across remarks, as well as providing more support (de la Peña et al, 2012) and listening more to clients' personal goals (Diamond, Hogue, Liddle, & Dakof, 1999). During the delivery of the final message, clients' oppositional behavior is an invitation for therapists to restrain themselves and not insist on proposing a homework task that is being rejected by their clients.…”
Section: Therapeutic Interaction Dropout and Compliance With Homewomentioning
confidence: 96%